Echolucency of the Carotid Artery Intima‐Media Complex and Intima‐Media Thickness Have Different Cardiovascular Risk Factor Relationships: The Women's Interagency HIV Study. Issue 2 (19th February 2015) - Jung, Molly; Parrinello, Christina M.; Xue, Xiaonan; Mack, Wendy J.; Anastos, Kathryn; Lazar, Jason M.; Selzer, Robert H.; Shircore, Anne M.; Plankey, Michael; Tien, Phyllis; Cohen, Mardge; Gange, Stephen J.; et al.
Abstract : Background: Adults infected with HIV have increased atherosclerosis potentially associated with both HIV and non‐HIV associated factors. We characterized risk factors for atherosclerosis as measured by noninvasive vascular imaging. Methods and Results: We used B‐mode ultrasound to examine levels and correlates of echogenicity and vessel wall thickness of the carotid artery intima‐media complex in 1282 HIV‐infected and 510 HIV‐uninfected women of the Women's Interagency HIV Study. Levels of gray scale median (GSM, a measure of echogenicity) did not vary between HIV infection groups. In both groups, smokers had increased GSM, whereas age, diabetes, elevated blood pressure, and high BMI were associated with lower (rather than higher) GSM. Each of these non‐lipid CVD risk factors, especially age and blood pressure, was also associated with higher levels of carotid artery intima‐media thickness (cIMT). Higher serum triglyceride levels were associated with lower GSM in both HIV‐infected and HIV‐uninfected groups. Additional lipid risk factors for low GSM including high LDL cholesterol and low HDL cholesterol levels were identified in HIV uninfected but not in HIV infected women. In contrast to findings for GSM, among the lipid parameters only LDL cholesterol level had an association with cIMT, which was observed only in the HIV uninfected group. Conclusions: Lipid and non‐lipid risk factor associations with echolucency of the carotid artery and the thickness of the common carotid artery intima‐media layer suggest that these measures capture different aspects of atherosclerosis.